"Medianeras" Sidewalls - Gustavo Taretto - Sari, Tuba (Bentham Science Publishers, 2024)
Medianeras, which is closely related to architects and urban actors, deals with many subjects such as the standardization of the individual, standard life, display windows, lost spaces, capitalism, digitalized world, and relations. The focus of the narrative in the film, "Medianeras" is defined as the empty and windowless side walls of the buildings adjacent to the neighboring blocks. While the side walls are shown as the cause of physical separation between people in the city, these surfaces are also figured as the dead and vacant spaces of each building that serve no purpose. The scenario of the film, which begins with the architectural representation and criticism of the capital city of Argentina, Buenos Aires, is built through the parallel lives of the two characters. The metaphor of "sidewalls" used spatially in the film corresponds to a show alternately of the two narratives at similar moments. This spatiotemporal narrative in the film is linearly fictionalized within the sections of "A Short Autumn", "A Long Winter" and "Spring at Last" in the text. In the film, which reflects the architectural differences of the city of Buenos Aires through the subjective narrative of the characters Martin and Mariana, similar relationships are defined between urban structures and people living in the city. The internal monologues quoted through the voices of Martin and Mariana touch upon many universal city and urbanite problems on the axis of the individual-society world through the life experiences of the characters. By establishing a similarity between human life and building, the unplanned development and architecture of the city are held responsible as the cause of social and physical problems. By establishing a similarity between human life and building, the unplanned development and architecture of the city are held responsible as the cause of social and physical problems. In the face of the legitimation of the internet as a communication technology, it connects the feeling of loneliness and virtual-real-world contradictions with unplanned urbanization in metropolises caused by unplanned urbanization. Whereas the architectural representation of the city is expressed in the space-time coexistence of the characters, it facilitates comprehension by emphasizing the experiences of private living spaces and urban public spaces. © 2024 Bentham Science Publishers. All rights reserved.
Keywords: Architecture; Buenos Aires; Capitalism; City; Environment; Experience; Human; Image; Individual; Internet; Living space; Medianeras; Metropolis; Movie; Sidewalls; Society; Space; Time; Unplanned urbanization; Virtual-real world